Analysis of The Influence of Burnout, Job Satisfaction and Organizational Commitment on Turnover Intention of Electronic Manufacturer Employees in Indonesia - Joko Ariawan; Budi Akhmad Tarigan; Ainil Mardiah; Febri Sari Siahaan; La Mema Parandy (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
With organizational commitment acting as an intermediary variable in the study's analysis of the relationship between burnout and job satisfaction and intention to leave, employees. Nonprobability sampling methods with saturated sampling types are used in this sampling methodology. Using a Likert scale with five categories, the questionnaire asks for information. The data analysis method employed in this inquiry is the route analysis method. The analysis used in this study includes a validity test, a reliability test, a normality test, a coefficient of determination test, an f-test, a t-test, and a Sobel test to determine the mediating effect. The study's results show that burnout affects organizational commitment, job satisfaction affects organizational commitment, burnout and job satisfaction both affect organizational commitment, burnout affects turnover intention, job satisfaction affects turnover intention, organizational commitment affects turnover intention, and burnout toward work affects organizational commitment.